2018
DOI: 10.1111/ipd.12378
|View full text |Cite
|
Sign up to set email alerts
|

Is parental oral health literacy a predictor of children's oral health outcomes? Systematic review of the literature

Abstract: Low parental OHL was associated with dental caries among their children. It is too soon to assume an association between OHL and the remaining outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 28 publications
4
53
0
7
Order By: Relevance
“…Similar findings have been obtained in studies focusing on adults . Moreover, a high level of OHL on the part of parents/guardians seems to have a preventive effect regarding the occurrence of dental caries in children . When studying adolescents, however, it is important to consider their own levels of OHL.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar findings have been obtained in studies focusing on adults . Moreover, a high level of OHL on the part of parents/guardians seems to have a preventive effect regarding the occurrence of dental caries in children . When studying adolescents, however, it is important to consider their own levels of OHL.…”
Section: Discussionsupporting
confidence: 80%
“…For the purposes of this paper, early adolescence is considered to be 12 years of age. Moreover, studies of this nature involving children have used the OHL of parents/guardians (proxy measure) . As early adolescence is a period in which individuals gain greater autonomy, it is important to consider the level of OHL among early adolescents and how it influences the development of dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the MOHS-TC may partly explain these ndings. Studies have shown that children of parents with lower levels of health literacy exhibit fewer healthy behaviors [24] ; thus, parents' oral health literacy level in uences their children's oral health [25] . The older generation has been in uenced by traditional concepts, and their cognition on brushing, ossing, teeth cleaning and tooth extraction is not comprehensive enough [26].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to obtain, process, and understand health information will help them to seek health care, if needed, and to participate in health promotion and disease prevention measures. It is also known that poor health literacy of parents is associated with a reduced understanding of preventive care information, lower access to preventive care services and quite often with undesirable health exposures and outcomes for children including poor nutrition, obesity, poor oral health, exposure to second-hand tobacco smoke, higher rates of injury, mistakes in the administration of drugs, or unnecessary visits to emergency departments [10,11]. The health literacy of parents, families, and other people in the social context of children is critical for their health and wellbeing and needs to be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%